Acute cerebellar ataxia as the first manifestation of Imerslund-Gräsbeck syndrome - Eslamieh, Hossein (Iranian Journal of Child Neurology, 2021)
Imerslund-Grasbeck syndrome is a rare condition caused by Vitamin B12 deficiency and proteinuria. In this article, we reported a 10-year-old girl with imbalance and urinary incontinence. This case had cerebellar ataxia as the first manifestation. The disequilibrium had been progressed gradually wihin 3 weeks and was consistent with the symptoms of cerebellar involvement and urinary incontinence. Brain and cervicothoraco lumbar MRI was normal. In labratoary examinations, in addition to macrocytic anemia the patient had elevated lactate dehydrogenase (4775) so the possibility of malignancy raised, therefore bone marrow aspiration performed, In bone marrow examination hypercellular marrow with megaloblastic changes observed. This data proved megaloblastic anemia. Investigation of serum levels of vitamin B12 showed it was lower than normal range and the patient had significant proteinuria with normal nephrologic investigations. gasterointestinal tract study showed no evidence of serious problem and metabolic studies were normal . Finally, based on datas, Imerslund-Gräsbeck syndrome was recognized. Patient treated by Vitamin B-12 Injection and it led to improvement of balance, so that, after a month, He was able to walk and the cerebellar symptoms were greatly gone however proteinuria persists.